Structure, Disturbance, and Change in the Bristlecone Pine Forests of Colorado, U.S.A. - Baker, William L. (Arctic and Alpine Research, 1992)
To analyze trends in the structure of forests dominated by Colorado bristlecone pine (Pinus aristata Bailey) the author sampled size class structures, collected environmental data, and determined the approximate year of origin of these forests at 65 sites scattered throughout the range of P. aristata in Colorado. Cluster analysis and detrended correspondence analysis (DCA) were used to identify major trends in the size class data. The size class data suggest that P. aristata is a long-lived species that primarily regenerates following fires. The DCA results suggest that (1) the major trend in variation in structure was related to time since disturbance, and (2) Populus tremuloides Michx. is present as numerous small stems in some of the P. aristata forests regardless of the age of these forests, a role for P. tremuloides that is at odds with the traditional view of this tree as primarily a seral species in the Rocky Mountains. Many P. aristata stands originated near A.D. 1900 and between A.D. 1625 and 1700. These were warm, dry periods that might have promoted fires, and they were also periods when sunspot numbers were low. The Southern Oscillation Index did not correlate with times of abundant stand origins. Although many P. aristata forests are over 500 yr old, these forests do not appear to be stable or unchanging.